Development of a PVC Membrane Potentiometric Sensor with Low Detection Limit and Wide Linear Range for the Determination of Maprotiline in Pharmaceutical Formulations. Issue 2 (14th January 2022) - Tekce, Serkan; Subasi, Yaver; Coldur, Fatih; Kanberoglu, Gulsah Saydan; Zahmakiran, Mehmet
Abstract: Maprotiline (MAP), is an active ingredient of some antidepressants which has been broadly used for the therapy of depression. The overdose of MAP in the treatment of patients with depression can lead to significant side effects, even lethal intoxication. Therefore, it is very important to develop simple, inexpensive, fast and reliable detection methods for MAP in interested samples. In our present study, we have offered a novel poly(vinylchloride) (PVC) membrane maprotiline‐selective potentiometric sensor based on a type of MOFs, known as MIL‐53(Al), as electroactive ionophore substance. The sensor prepared at the optimum membrane composition exhibited a linear response for maprotiline hydrochloride in the concentration range of 1, 0×10 −9 M−1, 0×10 −2 M with a slope of 59, 1 mV/decade and detection limit of 9, 0×10 −10 M. The pH working range of the sensor was determined as 2, 0–9, 5. The response time of the sensor was very fast and less than 5 s. With these performance features, it has been shown that the current sensor has quite superior features compared to the potentiometric MAP‐selective sensor available in the literature. The potentiometric application of the sensor was successfully carried out with the detection of MAP in pharmaceutical tablets containing MAP‐HCl. Abstract : A novel PVC membrane maprotiline‐selective potentiometric sensor with improved linear range and detection limit based on a metal oxide framework (MIL‐53(Al)) was described for reliable determination in pharmaceutical samples. The developed sensor was successfully employed for maprotiline determination in drug tablets and highly acceptable results were obtained statistically when compared to the analysis results of GC‐FID.